The Effect of Skimming Method towards Students’ Reading Comprehension - Firmadini, Firmadini; Masrul, Masrul (Universitas Pahlawan Tuanku Tambusai, 2024)
This experimental research was carried out in the second semester of the English Education Study Program, Faculty of Teacher Training and Education, Universitas Pahlawan Tuanku Tambusai. This study aims to determine the effect of the Skimming Method on students' reading comprehension. The research methodology uses a pre-experimental design. The sample of this research is the second semester formed in one group using the Pretest and Post-test. Consists of 32 students. This study used a total sampling technique which involved all English Language and Education students in the second semester. The instrument used in this study was a reading comprehension test. Data were analyzed using the SPSS 16 program. Based on data analysis, the study showed that the average post-test score of experimental class students was 87.59 and the average pre-test score was 38.62. So the difference is 48.97. Data analysis showed a significance (2-tailed) 0.000 0.05, which means that Ha is accepted. It can be concluded that there is an influence on the use of the Skimming Method on students' reading comprehension.